Novel Von Hippel-Lindau Germline Variants in Iranian Patients with Retinal Capillary Hemangioblastoma - Fatemeh Azimi; Kowsar Bagherzadeh; Golnaz Khakpoor; Saeed Talebi; Ahad Sedaghat; Reza Mirshahi; Hengameh Kasraei; Reza Afshar Kiaee; Masood Naseripour (Case Reports in Ophthalmology)
Introduction: The aim of this study was to determine the potential genetic cause of retinal capillary hemangioblastoma (RCH) with symptoms of Von Hippel-Lindau (VHL) disease. Case Presentations: Three Iranian families (5 RCH patients) with novel variants are included in this study. The VHL variant analysis was performed by the Sanger sequencing technique. Molecular dynamics (MDs) simulations were conducted to analyze conformational changes resulting from variants in VHL protein structure and were compared with that of the native structure. Novel variant sites, including c.511A>C, c.511A>T, and c.514C>T in exon 3 of the VHL gene were identified. According to the American College of Medical Genetics (ACMG) classifications, c.514C>T (p.P172S) and c.511A>C (p.K171Q) are classified as variants of uncertain significance (VUS), and c.511A>T (p.K171*) is classified as a likely pathogenic variant. MD simulations demonstrated overall fluctuations of the proteins structure and a significantly lower degree of flexibility in the α-domain for the variant-encoded VHL protein structure compared to that of the native form. Conclusion: The structural information and computational analysis of the identified variants are predicted to induce conformational changes that limit the flexibility of protein VHL interaction interface with Elongin B/C, Elongin C/B, and Cullin-2, which are necessary for hypoxia-inducible factor 1-α binding. The genetic variants identified in Iranian patients with RCH may aid in the molecular confirmation of other patients diagnosed with VHL and their at-risk family members. These pioneering results that include detailed structural and functional analysis of a variant’s effect on the VHL protein may serve as a model for future studies.